MEREDUKSI DAMPAK PSIKOLOGIS KORBAN BENCANA ALAM MENGGUNAKAN METODE BIBLIOTERAPI SEBAGAI SEBUAH PENANGANAN TRAUMA HEALING [REDUCING THE PSYCHOLOGICAL IMPACT OF NATURAL DISASTER VICTIMS USING BIBLIOTHERAPY METHOD AS A TRAUMA HEALING HANDLER] - Hayatul Khairul Rahmat; Arief Budiarto (Journal of Contemporary Islamic Counselling, 2021)
This paper tried to explain bibliotherapy as handling trauma healing to reduce the psychological impact of victims of natural disasters. Indonesia is a country that will experience a disaster that can be seen based on data from the National Disaster Management Agency in 2019 provided 3.721 disaster events. Disasters that occur will cause both psychological impact and non-psychological impact. Victims of natural disasters that can be seen from the physical, emotional, behavioral, and cognitive aspects. Bibliotherapy is one of the service techniques by providing reading material about people who solve problems more similar to the counselee and finally can overcome difficulties or reading material that can improve the counselee's thinking to be more rational. This bibliotherapy will increase counselee's way of thinking to be more rational and also as a means of healing trauma. This study used a literature study by examining several theories and literature relating to bibliotherapy steps as a treatment for trauma healing to reduce the psychological impact of victims of natural disasters.